Development of a computational instrument using a lagrangian particle method for physics teaching in the areas of fluid dynamics and transport phenomena - Fraga Filho,Carlos Alberto Dutra (2017)
Abstract Particle methods are an alternative to the traditional mesh Eulerian methods for solution of fluid dynamics and transport phenomena problems. The Lagrangian Meshless Smoothed Particle Hydrodynamics (SPH) method presents advantages compared to mesh methods as a better visualisation of the spatio-temporal evolution of the flow (and the fluid properties), and a lower computational cost in the study of complex geometries with topological changes, or free surfaces. A computer code has been written for serial computation using FORTRAN Programming Language. Three classical physical problems have been simulated: diffusion in a flat plate, still fluid within an immobile reservoir and dam breaking. In code validation, numerical results obtained showed a good agreement with the analytical and experimental results reported in the literature. The numerical code developed and presented in this work is a valuable tool for the teaching of Physics.